The invention of the world again... Megastructural movement in Spain, 1960-1970 - García Martínez, Mónica; Muñoz Pardo, María Jesús (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
Between 1960 and 1970 a handful of Spanish architects proposed a series of projects that could be qualified as megastructures. The concept of megastructure emerged like a last attempt by architecture to maintain control over the project and the territory at a time when participation of the individual in shaping the city was increasingly more in demand. Spanish architecture, that began to open itself to the exchange of foreign theories and practises after decades of isolation, will incorporate the concept of megastructure, with its peculiarities and discrepancies in relationship to the international scene. This study aims to examine the production of megastructures in Spain as a whole: historical background, genesis, types, production areas and phases of development. The main objective is to re-read a number of projects that have been designed over a decade, and although in principle they appear fragmented, their review from a megastructural perspective allows us to build a global vision. We believe it is precisely this overview which can best contribute to the definition of one ́s own corpus, recognizable and comparable with international panorama, so that registration of Spanish megastructural experiences within the framework of international culture can be made easier.